2001
DOI: 10.1590/s0100-879x2001001100013
|View full text |Cite
|
Sign up to set email alerts
|

Biflavonoids inhibit the production of aflatoxin by Aspergillus flavus

Abstract: The biflavonoids 6,6"-bigenkwanin, amenthoflavone, 7,7"-dimethoxyagastisflavone and tetradimethoxybigenkwanin isolated from Ouratea species were tested for inhibitory activity on Aspergillus flavus cultures. Suspensions of Aspergillus flavus spores were inoculated into 50 ml of YES medium at different biflavonoid concentrations: 5 and 10 µg/ml for 6,6"-bigenkwanin, amenthoflavone and 7,7"-dimethoxyagastisflavone, and 5, 10, 15 and 20 µg/ml for tetradimethoxybigenkwanin. The four biflavonoids showed inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
0
19
0
2
Order By: Relevance
“…O óleo extraído do extrato hexânico dos frutos de Ouratea parviflora apresentou atividades antibacteriana e antifúngica 30 . Os biflavonóides isolados de O. spectabilis, O. multiflora e O. parviflora mostraram inibição da produção de aflatoxina por Aspergillus flavus 31 .…”
Section: Aspectos Farmacológicos E Importância Econômica De Algumas Eunclassified
“…O óleo extraído do extrato hexânico dos frutos de Ouratea parviflora apresentou atividades antibacteriana e antifúngica 30 . Os biflavonóides isolados de O. spectabilis, O. multiflora e O. parviflora mostraram inibição da produção de aflatoxina por Aspergillus flavus 31 .…”
Section: Aspectos Farmacológicos E Importância Econômica De Algumas Eunclassified
“…Some flavonoids and biflavonoids are biologically active against A. flavus and A. parasiticus (7,10,11). In this work, two active flavonoids were isolated from P. sonchifolia leaves.…”
Section: Discussionmentioning
confidence: 98%
“…2). The chemical analyses of compound 1 showed a higher oxidation pattern than compound 2, and the oxidation pattern of the flavonoids and their position could be responsible by AFB1 production inhibition (7,10). Norton, 1999, reported that highest AFB 1 inhibition was obtained with 3-OH compounds, which were three times more active than the related 3-deoxy compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of aflatoxins was determined by photodensitometry (Shimadzu, CS 9000) comparing the area and density of the spot samples with aflatoxins B 1 , B 2 , G 1, and G 2 standards (Sigma Aldrich, USA) (GONÇALEZ et al, 2001). The detection e quantification limits were established how the lowest fluorescence detectable signal and the lowest concentration measured, respectively.…”
Section: Aflatoxin Analysesmentioning
confidence: 99%